Scenario of prevalence and socio-environmental conditions associated with soil-transmitted helminth infections in Brazil: An integrative review study (Research, Society and Development, 2021)
The objective was to know the prevalence and socio-environmental conditions of the Brazilian population affected by soil-transmitted helminth infections in the last ten years. Exploratory and descriptive study of integrative literature review with time frame from 2010-2020. Search performed in four open access databases. Descriptive statistics used for calculations of prevalence of soil-transmitted helminth and socio-environmental data. A total of 841,107 human samples were included in the 55 studies eligible for this review. The combined prevalence of soil-transmitted helminth in the country was 19%. Ascaris lumbricoides (68%) was the most prevalent, followed by hookworms (24%) and Trichuris trichiura (8%). High prevalence was observed in the Midwest (22%), Northeast (19%) and North (14%). Poor sanitation, inadequate hygiene habits and low income were the factors associated with soil-transmitted helminth infections most reported in the studies. Soil-transmitted helminth infections are still prevalent in the country although it has dropped slightly in the past five years. As with the global trend, Ascaris lumbricoides was the most prevalent soil-transmitted helminth. Among the main factors associated with infections, poor sanitation, inadequate hygiene habits and low income stand out. We hope that the results of this review will serve as a contribution to public policies and regional administrations with programs to raise awareness among the population about prevention and care not to spread the infection, in addition to investments in infrastructure in the garbage collection sector, sewage system, water treatment and expand the mass administration of antiparasitic treatments in Brazil.